2004
DOI: 10.7861/clinmedicine.4-3-235
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous endoscopic gastrostomy: an effective strategy for gastrostomy feeding in patients with dementia

Abstract: -Percutaneous endoscopic gastrostomy (PEG) is an accepted technique for longterm enteral feeding. Its use has increased because of its simplicity and low complication rate. The demands for gastrostomy insertion have risen and now encompass indications where the long-term outcomes are uncertain. Dementia has become one of the commonest indications for gastrostomy feeding. This article reviews the justification for PEG feeding in dementia and suggests a practical approach for this difficult clinical situation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
1
15
0
2
Order By: Relevance
“…5 The natural history of dementia may make it appear as if the patient is 'starving to death' and therefore it has previously been one of the most common indications for PEG insertion. 1 This has caused much debate, as it has been suggested that a basic duty of doctors is to provide adequate nutrition for patients. 6 However, several studies have found that PEG feeding this group of patients does not prolong their lives, with no increase in nutritional markers after tube placement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 The natural history of dementia may make it appear as if the patient is 'starving to death' and therefore it has previously been one of the most common indications for PEG insertion. 1 This has caused much debate, as it has been suggested that a basic duty of doctors is to provide adequate nutrition for patients. 6 However, several studies have found that PEG feeding this group of patients does not prolong their lives, with no increase in nutritional markers after tube placement.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although an overall reduction in the number of referrals for PEG insertion was observed between 2001 and 2006, a proportion were still deemed unsuitable after review by the NNS. In an attempt to address this, the referral form was introduced which included additional information for referring doctors to aid them in the decision-making process about suitability for PEG insertion.…”
Section: Implementation Of Referral Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Aus mehreren Gründen kann entgegen den viel zitierten Auffassungen mancher Autoren [22,26] [42,60], Hypoalbuminämie [48], fortgeschrittene Demenz [65], Aspirationsereignis im letzten Jahr [42], Pneumonie, Schluckstörun-gen, Komorbiditäten (für eine ausführ-lichere Übersicht siehe [66]). …”
Section: Zusammenfassungunclassified
“…The use of cardiopulmonary resuscitation, artificial feeding (in particular feeding by percutaneous endoscopic gastrostomy), 1 and of mechanical ventilation has posed dilemmas regarding the appropriateness of artificially keeping alive patients who are incapacitated with no hope of recovering function, or are dying from their disease. 2 These tools, inappropriately used, can deny patients the comfort of dying with dignity.…”
mentioning
confidence: 99%